A new species of stilt-legged mite of the genus Neophyllobius Berlese (Acari: Camerobiidae) from Brazil - Escobar-Garcia, Hector Alonso [UNESP]; de Andrade, Daniel Júnior [UNESP]; Mohammad-Doustaresharaf, Mojtaba; Ueckermann, Edward A. (Les Amis d'Acarologia, 2024)
A new species of Neotropical Camerobiidae from Brazil, Neophyllobius (Neophyllobius) unespensis n. sp., is collected and described from the raceme-type inflorescences of a native South America forest tree, Cannonball tree, Couroupita guianensis Aubl. (Lecythidaceae), description based on females, a protonymph, and a larva. The new stilt-legged mite was found during two springs for two consecutive years, which coincides with the inflorescence period of this tree.
Keywords: systematics; Prostigmata; Raphignathoidea; free-living predatory mites; forest tree